Microteaching Based Blended Learning at University - Supardi Supardi (Khazanah Multidisiplin, 2023)
The purpose of this study is to construct learning methods that are relevant in microteaching learning using a blended learning approach, namely combining offline face-to-face learning with e-learning. The research method uses classroom action research with two cycles. In the first cycle of digital-based learning (synchronous) and the second cycle using direct learning (asynchronous). Each cycle goes through CAR procedures such as: planning, implementing, observing, and reflecting. The results of this study indicate that microteaching based on blended learning gives a positive nuance to students' ability to practice basic teaching skills, especially skills in opening lessons. The asynchronous approach provides best practice experience for students on how to open lessons properly and the synchronous approach provides insight and additional experience for students to be able to adapt to advances in science and technology in the industrial era 5.0.